ISOLATION AND EVALUATION OF EFFECT OF CARBON AND NITROGEN ON CELLULOSE DEGRADING MICROBES - A. V. GOMASHE,; S. A. WANKHADE,; M. J. MADHUGIRI, (The Bioscan, 2012)
The production and utilization of cellulolytic enzymes is a topic of great interest in the world searching for renewable resources. A study was done to determine the effect of Carbon and nitrogen sources on the growth of different microbes isolated from different soil samples. Among the 40 isolates, 7 isolates showed higher activity as compare to others .To carry out the study, nine different carbon sources and seven different nitrogen sources were used. Among the carbon sources used, maximum growth was observed in glucose followed by other carbon sources, whereas urea, showed potent result in comparison to other nitrogen sources for better survival of cellulose degrading bacteria.